Strong Surface‐Bound Sulfur in Carbon Nanotube Bridged Hierarchical Mo2C‐Based MXene Nanosheets for Lithium–Sulfur Batteries - Lv, Li‐Ping; Guo, Chao‐Fei; Sun, Weiwei; Wang, Yong (Small (Weinheim an der Bergstrasse, Germany), 2019)
In this work, hydroxyl‐functionalized Mo2C‐based MXene nanosheets are synthesized by facilely removing the Sn layer of Mo2SnC. The hydroxyl‐functionalized surface of Mo2C suppresses the shuttle effect of lithium polysulfides (LiPSs) through strong interaction between Mo atoms on the MXenes surface and LiPSs. Carbon nanotubes (CNTs) are further introduced into Mo2C phase to enlarge the specific surface area of the composite, improve its electronic conductivity, and alleviate the volume change during discharging/charging. The strong surface‐bound sulfur in the hierarchical Mo2C‐CNTs host can lead to a superior electrochemical performance in lithium–sulfur batteries. A large reversible capacity of ≈925 mAh g−1 is observed after 250 cycles at a current density of 0.1 C (1 C = 1675 mAh g−1) with good rate capability. Notably, the electrodes with high loading amounts of sulfur can also deliver good electrochemical performances, i.e., initial reversible capacities of ≈1314 mAh g−1 (2.4 mAh cm−2), ≈1068 mAh g−1 (3.7 mAh cm−2), and ≈959 mAh g−1 (5.3 mAh cm−2) at various areal loading amounts of sulfur (1.8, 3.5, and 5.6 mg cm−2) are also observed, respectively. Mo2C‐based MXene nanosheets composited with carbon nanotubes are synthesized and used as sulfur host in lithium–sulfur (Li–S) batteries. The hydroxyl‐functionalized surface of Mo2C suppresses the shuttle effect of lithium polysulfides (LiPSs) through strong interaction between Mo atoms on the MXenes surface and LiPSs, leading to a superior electrochemical performance in Li–S batteries.